Benzimidazolyl phosphates as anti‐wear additives in poly(ethylene glycol) for steel/steel contacts. (29th January 2013) - Qiao, Dan; Wang, Haizhong; Feng, Dapeng
ABSTRACT Four novel benzimidazolyl phosphates (BPs) were synthesized and evaluated as anti‐wear additives in poly(ethylene glycol) for steel/steel contacts. The friction experiments were carried out on an Optimol SRV‐I oscillating reciprocating friction and wear tester (SRV) both at room temperature and high temperature. The worn surfaces of the steel discs were analysed by JSM‐5600LV scanning electron microscope and PHI‐5702 multifunctional X‐ray photoelectron spectrometer. It was indicated that poly(ethylene glycol) with 2 wt% BP additives had better friction‐reducing and anti‐wear properties than the commercial lubricant additive, tricresyl phosphate. Excellent tribological performance of BPs could be ascribed to the formation of high quality boundary films that consisted of the ordered adsorption films and tribo‐chemical reaction films. Copyright © 2013 John Wiley & Sons, Ltd.